2007
DOI: 10.1007/s10694-007-0007-7
|View full text |Cite
|
Sign up to set email alerts
|

Using FDS to Simulate Smoke Layer Interface Height in a Simple Atrium

Abstract: This study examines the possible effects of various make-up air supply arrangements and velocities in an atrium smoke management system. Variations include velocities ranging from 0.5 to 3.0 m/s. The arrangement of make-up air supply injection points include symmetrically located vents placed low in the spaced, an array of vents distributed from the floor to the ceiling, and asymmetrically located vents. Fire Dynamic Simulator version 4.06 is applied to simulate ten scenarios in a 30.5 m cubical domain with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 4 publications
1
44
0
Order By: Relevance
“…The least-square method [13,27] as well as the npercent (N = 30%) method [14,26] have been assessed by means of absolute and relative discrepancies, the latter being calculated with respect to the total atrium height (20 m). These two methods have been used to assess their accuracy in representing the smoke layer height.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The least-square method [13,27] as well as the npercent (N = 30%) method [14,26] have been assessed by means of absolute and relative discrepancies, the latter being calculated with respect to the total atrium height (20 m). These two methods have been used to assess their accuracy in representing the smoke layer height.…”
Section: Resultsmentioning
confidence: 99%
“…-Wall A. Twelve thermocouples were installed in three thermocouple trees to measure the temperature at 30 cm from the wall A (sensors [14][15][16][17][18][19][20][21][22][23][24][25] as can be observed in Figure 2c. These measurements are used to study the smoke temperature at the far field and the smoke layer drop.…”
Section: Fire Experiments and Simulations In A Full-scale Atrium 53mentioning
confidence: 99%
See 1 more Smart Citation
“…As it has been commented before, some works [12,[16][17][18] have shown that make-up air velocities of the order or larger than 1 m/s can disturb considerably both the fire and plume and, thus, can have a significant influence on the fire-induced conditions. However, in a previous work [12], different venting conditions were analyzed, including make-up velocities larger than 1 m/s, not finding any significant influence of these velocities on the inner conditions' evolution, for the specific cases studied.…”
Section: Discussion Discrepancies Between the Numerical Simulationsmentioning
confidence: 99%
“…In the recent years, some researchers have dealt with this make-up air issue, such as the studies from Hadjisophocleous and Lougheed [14], Yi et al [15] or Kerber and Milke [16] on the influence of the vents location and arrangement, as well as inlet velocities, on the fire-induced conditions. These works were conducted considering different shaped and sized atria and gave guidance on these matters, finding advisable to supply the fresh air below the theoretical smoke layer height, within a symmetric venting topology and at velocities lower than 1 m/s, to avoid plume perturbations, which reinforced the requirements and goals of the abovementioned fire codes.…”
Section: Introductionmentioning
confidence: 99%